The relationship between pedagogical competence and teacher self-efficacy on the ability to implement differentiated learning in public elementary schools - Agustin Nurochmah Hayati; Firmansyah; Anwar Novianto; Muhammad Alfatih Panatagama (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study examines the relationships among pedagogical competence, teacher self-efficacy, and the ability to implement differentiated learning among public elementary school teachers in Cluster 04, Jetis. The study employed a quantitative correlational design with an ex post facto approach. The study population comprised all teachers in public elementary schools in Cluster 04 Jetis and was drawn using simple random sampling. The instrument was a closed questionnaire that had been tested for validity and reliability. Data analysis was conducted using multiple linear regression. The results indicate that pedagogical competence and teacher self-efficacy are significant predictors of differentiated learning implementation, both as partial and as simultaneous predictors. In the partial analysis, pedagogical competence emerged as a strong positive predictor (b = 1.301, p < .05), whereas teacher self-efficacy exhibited a significant negative relationship (b = -.543, p < .05). The simultaneous test yielded a significant model (F = 62.271, p < .05), with a coefficient of determination (R2) of .762, indicating that the two variables collectively account for 76.2% of the variance in differentiated learning implementation. These findings suggest that while high pedagogical mastery is essential for adaptive instruction, general professional confidence without technical calibration may not yield optimal results. This research strengthens the scientific basis for teacher capacity development to improve the quality of adaptive learning in elementary schools.